Pengaruh Operasi Tangkap Tangan (OTT) terhadap Pelaporan Dugaan Tindak Pidana Korupsi oleh Masyarakat (Studi Kasus KPK) - Ardy Syahputra, Wardhana; Halley Yudhistira, Muhammad (Jurnal Kebijakan Ekonomi, 2023)
The Hand Arrest Operation (OTT) is an activity by the KPK in the field of cracking down on corruption that is well-known among the Indonesian people. The activity was also marked by a press conference which outlines the profile of the suspect and the chronology of the arrests. In carrying out its duties, the KPK cannot work alone. The active participation of the community is certainly very helpful for the KPK in carrying out its duties more effectively and efficiently, one form of which is by reporting suspected corruption crimes. The study was conducted to see how the OTT activities of the KPK affect public participation in reporting suspected corruption crimes. The data used are OTT activity data and KPK public complaints reports from 2017 to 2021. By using panel data regression ‘fixed effect model’, this study finds: every OTT activity followed by news dissemination through press conferences, becomes a signal in increasing the number public complaints to the KPK; OTT conducted on the island of Java has a significant contribution in increasing the number of public complaints compared to OTT outside Java; Annual data analysis shows that from 2019 to 2021, there is a downward trend in public complaints, especially in 2020 and 2021. This is in line with the very sharp decline in OTT compared to previous years. OTT that conducted in the political year did not affect the increase in public complaints, but on the contrary, outside the political year, the OTT had a significant effect on the increase in public complaints; The OTT that was carried out both in the year the Covid-19 pandemic occurred and the year before the pandemic, both had no effect on the increase in the number of public complaints.